Existence results to a nonlinear p(x)-Laplace equation with degenerate coercivity and zero-order term: renormalized and entropy solutions. Issue 2 (1st February 2016) - Li, Zhongqing; Gao, Wenjie
Abstract : This paper is devoted to the study of a nonlinear elliptic equation with degenerate coercivity, zero-order term and L 1 datum in the setting of variable exponent Sobolev space. The authors obtain the existence of renormalized solution and entropy solution via strong convergence of truncation. They also get some a priori estimates to the solution and the generalized gradient of the solution in the Marcinkiewicz space with variable exponent.